TRANSFORMASI SOCIAL SCIENCES PADA KURIKULUM NASIONAL (STUDI HISTORIS MAPEL IPS JENJANG SD, SMP, DAN SMA) - Sudrajat, Rahmat; Kumalasari, Dyah (FPIPSKR Universitas PGRI Semarang, 2023)
The development of Social Sciences (IPS) subjects in the national curriculum has undergone a significant transformation over time. At first, social studies teaching was based more on a traditional approach that focused on rote memorization of historical facts and geography. However, with the development of a more progressive educational approach, social studies underwent changes that included an interdisciplinary approach, the use of information technology, contextual teaching, and the empowerment of student skills. Changes in social studies teaching reflect the evolution of views on social science and educational goals Thus, these subjects no longer only focus on factual knowledge, but also introduce the social, economic, and political principles underlying social phenomena. Social studies aim to develop an in-depth understanding of the complexities of society and equip students with the critical thinking skills necessary to participate in modern society. The development of social studies also reflects changes in the issues emphasized in learning. Newer national curricula pay more attention to global issues such as climate change, international trade, and human rights. Social studies teach students about the social and environmental impacts of social policies and phenomena and encourage them to participate in positive social change. This research is descriptive qualitative research that explains how the transformation from time to time in Social sciences in the national curriculum. The results achieved in this study constitute the history of the development of social sciences.